PENGEMBANGAN MEDIA PEMBELAJARAN BUKU CERITA BERGAMBAR BERBASIS KEMAMPUAN MEMBACA PADA PEMBELAJARAN TEMATIK - Ayundha Rosvita; Indri Anugraheni (STKIP ROKANIA, 2021)
This research on the development of learning media for picture book learning has the objective of improving reading skills in grade 1 elementary school students, knowing the level of product validity tested by learning material experts and learning media experts. The validity of this product is carried out by the validator and the practitioner. The type in this research is Research and Development (R&D). The data collection technique in this study was carried out by going through the preliminary study stage. At this stage it is carried out through three stages, namely literature study, field survey, and preparation of product drafts. The data analysis technique in this study uses descriptive techniques. The results of this study found that the level of validity of the product development of picture story book learning media in improving the reading ability of grade 1 elementary school students according to material experts was getting a score of 40 with a percentage of 83% which is in the very high category and according to learning media experts getting a score of 70 with a percentage of 97% who are at very high scores